Effect of N2 flow rate on the properties of CNx thin films prepared by radio frequency plasma enhanced chemical vapor deposition from ethane and nitrogen - Othman, M.; Ritikos, R.; Khanis, N.H.; Rashid, N.M.A.; Gani, S.M.A.; Rahman, S.A. (2013)
Carbon nitride (CNx) thin films were deposited using radio frequency plasma enhanced chemical vapor deposition (rf PECVD) from a mixture of nitrogen (N2) gas and either methane (CH4) or ethane (C2H6) gases. The CH4 and C2H 6 flow rates were kept constant, while the N2 flow rate was varied. The effects of nitrogen incorporation on the growth rate and structural properties of the films were studied. The use of these two hydrocarbon precursors was also compared. It was found that the effects of N incorporation are significant for films deposited from the CH4 mixture and it greatly affects the bonding and optical properties of the films. In contrast, the effects of N incorporation on the films produced from C 2H6 are not as significant, though these films appear to be more uniform and show lower film porosity. Generally, the photoluminescence (PL) intensities increase with the increase in N incorporation for film deposited from both hydrocarbon mixtures. However, the PL properties of these CNx films are enhanced by the use of C2H6 as compared to CH4 since the films produced show lower defects. Â© 2012 Elsevier B.V.